Proof-of-Concept for Adjusted Surface Energies and Modified Fines as a Novel Concept in Particle Engineering for DPI Formulations - Nicholas Bungert; Mirjam Kobler; Regina Scherließ (MDPI AG, 2022)
Currently marketed dry powder inhaler (DPI) medicine lacks drug delivery performance due to insufficient powder dispersion. In carrier-based blends, incomplete drug detachment is typically attributed to excessive adhesion forces between carrier and drug particles. Adding force control agents (FCA) is known to increase drug detachment. Several researchers accounted this effect to a decrease in carrier surface energy (SE). In turn, an increase in SE should impede drug detachment. In this proof-of-concept study, we investigated the influence of the SE of the carrier material in binary blends by intentionally inverting the FCA approach. We increased SEs by dry particle coating utilising high-shear mixing, which resulted in decreased respirable fractions of the respective blends. Thus, we confirmed the SE of the carrier influences drug delivery and should be considered in formulation approaches. Complementing engineering techniques on the carrier level, we evaluated a method to modify the SE of extrinsic fines in ternary powder blends for inhalation. By the co-milling of fine lactose and an additive, we tailored the SE and hence the adhesiveness of additional fine excipients. Thus, the extent and the strength of drug-fines agglomerates may be controllable. For ternary DPI formulations, this work highlights the potential benefits of matching the SE of both fines and drugs.